2021
DOI: 10.1097/tp.0000000000003193
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic Clearance of a BK Virus-associated Metastatic Renal Allograft Carcinoma

Abstract: Background: Metastatic carcinoma of a renal allograft is a rare but life threatening event with a difficult clinical management. Recent reports suggested a potential role of BK polyomavirus (BKPyV) in the development of urologic tract malignancies in kidney transplant recipients. Case study: We investigated a kidney-pancreas female recipient with an history of BKPyV nephritis who developed a rapidly progressive and widely metastatic donor-derived renal carcinoma 9 years after transplantation. Histology and FIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 31 publications
(44 reference statements)
0
12
0
Order By: Relevance
“…Recently, the relationship between BKPyV and genitourinary malignant tumor, such as urothelial carcinoma [10,11] especially in bladder cancer [11][12][13] and renal cell carcinoma [14], has been reported. However, few studies suggested a potential role of BKPyV in the development of urologic tract malignancies in KTx recipients [15], and the association remains controversial. Herein, we describe a case of a KTx recipient with positive urine BKPyV replication who developed a graft pelvic tumor with positive immunohistochemical staining for simian virus 40 large T antigen (SV40 TAg).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the relationship between BKPyV and genitourinary malignant tumor, such as urothelial carcinoma [10,11] especially in bladder cancer [11][12][13] and renal cell carcinoma [14], has been reported. However, few studies suggested a potential role of BKPyV in the development of urologic tract malignancies in KTx recipients [15], and the association remains controversial. Herein, we describe a case of a KTx recipient with positive urine BKPyV replication who developed a graft pelvic tumor with positive immunohistochemical staining for simian virus 40 large T antigen (SV40 TAg).…”
Section: Introductionmentioning
confidence: 99%
“…Our recent work suggests that alarming innate and adaptive immune responses may be delayed in the late phase of BKPyV replication [ 17 ]. Finally, we speculate that LTag-targeted CD8 T-cell responses including those directed against the N-terminus shared with small T-antigen [ 37 ] may protect against BKPyV-associated urothelial carcinoma expressing solely LTag or truncated derivatives from chromosomally integrated BKPyV genomes [ 8 , 9 ], when there is little or no Vp1 expression [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…BK polyomavirus (BKPyV) is an opportunistic pathogen causing polyomavirus-associated hemorrhagic cystitis (PyVHC) in 5–20% of allogeneic hematopoietic stem cell (HSCT) recipients [ 1 , 2 , 3 ] and polyomavirus-associated nephropathy (PyVAN) in 1–15% of kidney transplant (KT) patients [ 4 , 5 ]. Moreover, PyV-associated urothelial cancer (PyVUC) has been recognized as an emerging entity in immunosuppressed patients with a history of prolonged BKPyV-replication and nephropathy following accidental integration of the BKPyV genome into human host cell chromosomes [ 6 , 7 , 8 , 9 ]. Uncontrolled BKPyV replication due to insufficient BKPyV-specific immunity appears to be the common denominator of these three major BKPyV diseases [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In their case, rejection of the pancreas resulted in a spontaneous rupture of a pseudoaneurysm of the pancreas arterial anastomosis requiring emergent surgery. 10 To our knowledge, there is no other literature on the successful treatment of metastatic donor-derived malignancy in SPK recipients.…”
Section: Discussionmentioning
confidence: 99%